Relationship between Economic Growth and Unemployment Rates in the Algerian Economy: Application of Okun’s Law during 1991–2019 - Louail, Bilal; Benarous, Djamel (Organizations and Markets in Emerging Economies, 2021)
This paper aims to examine the Algerian economy by applying Okun’s law to study the impact of real GDP on unemployment rates and examine the impact of labour market protection policies on Okun’s coefficients. The annual data on the Algerian economy for the period 1991–2019 were used. The autoregressive distributed lag (ARDL) bounds testing technique model was used in conjunction with the gap version for Okun’s coefficients. The empirical results show that Okun’s law operates in Algeria’s economy. Coefficients estimated using the gap version led to the conclusion that there was a negative and significant impact of the GDP gap on unemployment rates. Though there was a decline in unemployment as GDP increased, the rise in employment was very weak for each 1% increase in the GDP. These findings should be of significant interest to regulators and policymakers in the Algerian economy, practitioners and academic researchers, international and national investors, managers and any other groups interested in the labour market in the Algerian economy and the labour markets of other developing economies. The paper provides the real GDP’s effect on unemployment rates in Algeria by releasing the gap version for Okun’s coefficient. Also, it provides evidence that increased labour market protection mitigates the adverse effects of a decrease in output growth rate on employment.